MOTIVASI PEREMPUAN MELAKONI PERAN MAMAK DALAM SASTRA WARNA LOKAL MINANGKABAU - Nurhaida Nuri; Efyuhardi Efyuhardi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
This study aims to study in depth about the motivation of women melakoni mamak role that actualized in Minangkabau local color literature works. The research method used is qualitative method with approach of structuralism (pure) and sociology of literature. Minangkabau (kaba, novel, and short story) selected based on several considerations (purposive sampling). Data analysis is done by using theory with triangulation technique. The results show that (1) the local color literature structure of Minangkabau, before independence generally raised the theme of moral problems with chronological flow, the beauty of a typical background with a simple character whose character was static, while after independence raised the theme of struggle for freedom and self-esteem with unkonvansional groove, (2) factors causing waning of the role of mamak, (a) government policy, (b) social status in the family (c) education of parents, (d) stream of modernization and globalization, (e) influence of Islamic family system, (f) there is no legal sanction, (g) absence of assertiveness of mamak, and (3) women’s motivation for the role of mamak is more dominated by the need for rewards, both low-level needs, while respecting others as well as high level needs, while the need for self-esteem.